Sosialisasi Covid-19: Bahaya dan Pencegahannya Terhadap Masyarakat Pekon Landbaw Kecamatan Gisting Kabupaten Tanggamus - Pandu Lungguh Pambudi; Fredi Ganda Putra (FOUNDAE (Foundation of Advanced Education), 2021)
The Community Service Program in the form of socialization was carried out on the basis of collaboration between KKN-DR students at UIN Raden Intan Lampung with Pekon Landbaw Officials, Gisting District, Tangamus Regency, Lampung to provide socialization to the community regarding the dangers of Covid-19 and how to prevent it. Based on the service carried out, there are still many people in Pekon Landbaw who have not followed the health protocol rules that have been set by the government. The method used in this community service activity is door to door socialization about the prevention of Covid-19 through clean living behavior. The purpose of this service is to anticipate and prevent the spread of the corona virus in the community of 20 families in Pekon Landbaw. The result of this service activity is that the people of Pekon Landbaw, Gisting District, Tanggamus Regency have the knowledge and ability to anticipate the spread of Covid-19 through clean living behavior and are more alert and calm in the face of the ongoing pandemic.